Development of the Rad Method for Administrative Service Information Systems (Case Study: Jiwa Baru Village) - Nur Alifa Islammia; Fajriyah; Nurmayanti (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Administrative services in Jiwa Baru Village are still handled manually, causing delays, data errors, and inefficiency. This study aims to develop a web-based administrative information system using the Rapid Application Development (RAD) method. RAD was chosen for its speed and iterative approach involving active user participation. The system includes features for document requests and digital archiving. Data were collected through interviews and observations in Jiwa Baru Village. The system was evaluated using black-box testing. The results show that the system improves service efficiency, reduces errors, and provides easier data access for both village officials and residents. This system supports more modern and transparent public service delivery.